Extended adjuvant intermittent letrozole versus continuous letrozole in postmenopausal women with breast cancer (SOLE): a multicentre, open-label, randomised, phase 3 trial. Issue 1 (January 2018) - Colleoni, Marco; Luo, Weixiu; Karlsson, Per; Chirgwin, Jacquie; Aebi, Stefan; Jerusalem, Guy; Neven, Patrick; Hitre, Erika; Graas, Marie-Pascale; Simoncini, Edda; Kamby, Claus; Thompson, Alastair; et al.
Summary: Background: In animal models of breast cancer, resistance to continuous use of letrozole can be reversed by withdrawal and reintroduction of letrozole. We therefore hypothesised that extended intermittent use of adjuvant letrozole would improve breast cancer outcome compared with continuous use of letrozole in postmenopausal women. Methods: We did the multicentre, open-label, randomised, parallel, phase 3 SOLE trial in 240 centres (academic, primary, secondary, and tertiary care centres) in 22 countries. We enrolled postmenopausal women of any age with hormone receptor-positive, lymph node-positive, and operable breast cancer for which they had undergone local treatment (surgery with or without radiotherapy) and had completed 4–6 years of adjuvant endocrine therapy. They had to be clinically free of breast cancer at enrolment and without evidence of recurrent disease at any time before randomisation. We randomly assigned women (1:1) to treatment groups of either continuous use of letrozole (2·5 mg/day orally for 5 years) or intermittent use of letrozole (2·5 mg/day orally for 9 months followed by a 3-month break in years 1–4 and then 2·5 mg/day during all 12 months of year 5). Randomisation was done by principal investigators or designee at respective centres through the internet-based system of the International Breast Cancer Study Group, was stratified by type of previous endocrine therapy (aromatase inhibitors only vs selective oestrogen receptor modulators only vs both therapies), and used permuted block sizes of four and institutional balancing. No one was masked to treatment assignment. The primary endpoint was disease-free survival, analysed by the intention-to-treat principle using a stratified log-rank test. All patients in the intention-to-treat population who initiated protocol treatment during their period of trial participation were included in the safety analyses. This study is registered with ClinicalTrials.gov, number NCT00553410, and EudraCT, number 2007-001370-88; and long-term follow-up of patients is ongoing. Findings: Between Dec 5, 2007, and Oct 8, 2012, 4884 women were enrolled and randomised after exclusion of patients at a non-adherent centre, found to have inadequate documentation of informed consent, immediately withdrew consent, or randomly assigned to intervention groups in error. 4851 women comprised the intention-to-treat population that compared extended intermittent letrozole use (n=2425) with continuous letrozole use (n=2426). After a median follow-up of 60 months (IQR 53–72), disease-free survival was 85·8% (95% CI 84·2–87·2) in the intermittent letrozole group compared with 87·5% (86·0–88·8) in the continuous letrozole group (hazard ratio 1·08, 95% CI 0·93–1·26; p=0·31). Adverse events were reported as expected and were similar between the two groups. The most common grade 3–5 adverse events were hypertension (584 [24%] of 2417 in the intermittent letrozole group vs 517 [21%] of 2411 in the continuous letrozole group) and arthralgia (136 [6%] vs 151 [6%]). 54 patients (24 [1%] in the intermittent letrozole group and 30 [1%] in the continuous letrozole group) had grade 3–5 CNS cerebrovascular ischaemia, 16 (nine [<1%] vs seven [<1%]) had grade 3–5 CNS haemorrhage, and 40 (19 [1%] vs 21 [1%]) had grade 3–5 cardiac ischaemia. In total, 23 (<1%) of 4851 patients died while on trial treatment (13 [<1%] of 2417 patients in the intermittent letrozole group vs ten [<1%] of 2411 in the continuous letrozole group). Interpretation: In postmenopausal women with hormone receptor-positive breast cancer, extended use of intermittent letrozole did not improve disease-free survival compared with continuous use of letrozole. An alternative schedule of extended adjuvant endocrine therapy with letrozole, including intermittent administration, might be feasible and the results of the SOLE trial support the safety of temporary treatment breaks in selected patients who might require them. Funding: Novartis and the International Breast Cancer Study Group.